In another country : colonialism, culture, and the English novel in India - Joshi, Priya (Columbia University Press, 2002)
Asking what Indian readers chose to read and why, In Another Country shows how readers of the English novel transformed the literary and cultural influences of empire. She further demonstrates how Indian novelists writing in English, from Krupa Satthianadhan to Salman Rushdie, took an alien form in an alien language and used it to address local needs. Taken together in this manner, reading and writing reveal the complex ways in which culture is continually translated and transformed in a colonial and postcolonial context.